PENGARUH E-EVALUATION BERSIKLUS TERHADAP PRESTASI BELAJAR KIMIA SISWA SMK - Hadibyono, Hadibyono (Universitas Negeri Surabaya, 2013)
This study aimed to know the effect of cyclical e-evaluation of learning achievement in chemistry at second class even semester in Multimedia of SMK Negeri 12 Surabaya. A set of learning was developed by modification of the development of the 3-P model of learning that adapted from Ibrahim. Planning applied in taking data is modification from design